Economic Value and Revenue Management Systems : An Integrated Business Management Model - Capocchi, Alessandro (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Filling a gap in existing literature on revenue management systems, this book explores the use of business strategies which are specifically designed to have a positive impact on economic and financial efficiency. Focussing on services within the tourism industry, the author takes a new approach and identifies dynamic pricing and service differentiation as key components of strategic management. Providing fresh insights into an ever-expanding sector, this book will be a useful tool for those studying business strategy and management, as well as value creation theory, as it ultimately presents an integrated business management model which will ensure sustainability.
1. Starting and Running a Business -- 2. Time in Entrepreneurship -- 3. Entrepreneurship, Business Cycle and Creation of Value -- 4. The Short-term Measurement of the Creation of Value: The Importance of Technical Efficiency -- 5. The Impact of Technical Inefficiency on Business Management -- 6. Revenue Management from a Business-economic Perspective -- 7. Revenue Management Systems Based on Dynamic Pricing -- 8. Revenue Management Systems Based on Capacity Allocation -- 9. The Measurement of Revenue Management Policies: RevPAR and Yield Rate -- 10. Economic Value and Revenue Management Systems: Case Studies.
Description based on publisher-supplied MARC data.
Keywords: Business enterprises -- Finance; Leadership; Macroeconomics; Management; Service industries; Tourism; Business Strategy/Leadership.; Business Finance; Macroeconomics/Monetary Economics//Financial Economics; Services; Tourism Management